Stepwise integrated soil assessment framework, to better understand the role of soil health in farmer decision-making in Malawi - CGIAR Research Program on Maize (2021)
Successful piloting of framework: Carried out at two medium-term CA on-farm trial sites in Malawi, with focus groups - both trial farmer group (6 farmers) and non-trial farmers (8–10 farmers); total of 3 focus groups per community.